TRANSFORMASI STRATEGI PEMASARAN DI ERA DIGITAL: PENDEKATAN Systematic Literatur Review - Zulfikar Akbar (ADISAM PUBLISHER, 2025)
The development of digital technology has drastically changed the marketing paradigm, forcing companies to adapt to new approaches that are more interactive and data-driven. This research aims to analyse the transformation of marketing strategies in the digital era through a literature study that examines various changes in traditional marketing methods towards digital. Using a Systematic Literature Review (SLR) approach, this research identifies the role of social media, technology, and e-commerce in changing the marketing landscape. The results show that social media has become a key channel for building interactive relationships with consumers through visual content and influencer marketing. Technologies such as big data, artificial intelligence, and marketing automation are also proven to increase the effectiveness of marketing campaigns by providing a more personalised experience. On the other hand, e-commerce platforms provide great opportunities for companies to expand market reach and improve competitiveness through promotions and loyalty programmes. The study also underlines the importance of innovation in marketing strategies to survive in an increasingly competitive market. This research makes an important contribution in understanding the dynamics of digital marketing and its implications for companies, especially in facing the challenges and opportunities that arise in the digital era